Spinal Neuronavigation for Lumbar Plate Fixation in Miniature Breed Dogs - Papacella-Beugger, Angela; Forterre, Franck; Samer, Eva; Guevar, Julien; Müller, Andrea; Planchamp, Bastien; Progin, Alexia; Schweizer, Daniela (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The main aim of this pilot study was to assess the feasibility of spinal neuronavigation for plate fixation of lumbar vertebrae in miniature breed dogs using a surgical navigation system in combination with a custom-made reference array.Study Design This was an experimental cadaveric study in five miniature breed dogs.Methods A 4-hole locking plate with four 2.0-mm locking screws was placed on two adjacent lumbar vertebrae using a neuronavigation system consisting of a mobile cone beam computed tomography linked to a navigation system. The procedure was performed by a novice surgeon. The plate and screw positions were assessed for surgical safety using predefined criteria. Surgical accuracy was determined by the deviation of entry and exit points between pre- and postoperative images.Results A total of five plates and 20 screws were placed. In 85% (17/20), screws were placed appropriately. The median entry point deviation was 1.8 mm (range: 0.3–3.7) and the median exit point deviation was 1.6 mm (range: 0.6–5).Conclusion Achievement of surgical accuracy in the placement of screws for fixation of lumbar vertebral plates in small breed dogs using neuronavigation with a custom-made reference array by a novice surgeon resulted in surgical safe plate placement in four of the five cadavers. Therefore, we judge the method as promising, however, further studies are necessary to allow the transfer of image-guided navigation for lumbar plate fixation into the clinic.
Keywords: canine; neuronavigation; lumbar; stealth station